Persistent disputes over the classification of defining rule (Hukum Taklifi): suggested resolutions - Abu Elgasim, Saad; Ansari, Abdul Haseeb; Arifin, Mahamad (INSI Publications, 2013)
Divine rule (Hukm shar‘i) has classically been defined as: “The communication of God (khitab Allah) concerning the conduct of the competent persons (af‘al al-mukallafin) by way of command (iqtida’), option (takhyir) anddeclaration (wad‘)”(Badran, n.d.).Classically too, the three ways by which the communication of Allah is concerned with the conduct of the competent person have been classified into two kinds: hukm taklifi and hukm wad‘i.hukm taklifi is concerned with the conduct of the competent person by way of command or option, and hukm wad‘i is concerned by way of declaration (Abd al-Wahhab, 1995).These two ways by which hukm taklifi is concerned with the conduct of the competent person have been further classified into several categories the number of which has been a subject of dispute. Dispute has also arisen over several issues discussed under these categories disputed. These disputes have persisted for as long as hukm taklifi itself has persisted, and therefore they are deemed to be inevitable. Some of these persistent disputes do not seem to be as inevitable as they are thought to be, and therefore this paper will attempt to resolve them. These persistent disputes pertain to the major classification of hukm taklifi into several categories as well as minor issues involved by the categories concerned. As for the major classification, the paper will consider the contentions made as to the number of its categories and the arguments made in their favour. As for the minor issues, similarly, the paper will consider the contentions made as to their nature and the arguments made in their favour. As for both, the paper will, having examined the arguments considered, prefer one contention to the other or others or, if not, suggest an alternative to them all.Having considered the contentions made and the arguments made in their favour, it is submitted that hukm taklifi is divisible into five categories as contended by the Jumhur and not seven as contended by the Hanafis. As contended by the Jumhur, though in a slightly different mode of reasoning, an act may be characterized by prohibition as well as obligation. Obligation, like prohibition, may never be collective, however it, unlike prohibition, may be elective.